Influence of Metal Oxides Impregnated on Silica—Alumina in the Removal of Sulphur and Nitrogen Compounds from a Hydrotreated Diesel Fuel Stream - E.B. Silveira; C.O. Veloso; A.L.H. Costa; C.A. Henriques; F.M.Z. Zotin; M.L.L. Paredes; R.A. Reis; S.S.X. Chiaro (Adsorption Science & Technology)
The environmental legislation of many countries imposes severe restrictions on the emissions of gaseous pollutants, including NO x and SO x . Efficient alternatives for the removal of nitrogen and sulphur contaminants are required to obtain increasingly cleaner fuels. In this regard, adsorption is economically promising, because it requires less energy than the traditional hydrotreating processes due to mild conditions of temperature and pressure required. The objective of this study was to evaluate the influence of nickel, cerium, molybdenum and cobalt oxides impregnated on silica–alumina in removing nitrogen and sulphur compounds from a hydrotreated diesel. The incorporation of metal oxides increased the density of acid sites and promoted the removal of nitrogen and sulphur compounds, especially the one impregnated with molybdenum oxide. The influence of molybdenum oxide loading was also studied. It was observed that this synthesis parameter affected acid sites density and contaminant removal.